2017
DOI: 10.1038/s41598-017-10326-w
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterisation of a Sarcoptes scabiei protein tyrosine kinase as a potential antigen for scabies diagnosis

Abstract: Scabies is a disease that harms humans and other animals that is caused by the itch mite Sarcoptes scabiei burrowing into the stratum corneum of the skin. In the early stages of scabies, symptoms are often subclinical and there are no effective diagnostic methods. Herein, we cloned, expressed and characterised an S. scabiei protein tyrosine kinase (SsPTK) and evaluated its diagnostic value as a recombinant antigen in rabbit during the early stages of Sarcoptes infestation. The SsPTK protein is ~30 kDa, lacks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…The optimal conditions for the rSsCLP5-based indirect ELISA were determined to be 4 μg/ml of rSsCLP5 protein, a 1:120 serum dilution, and a 1:3000 dilution of secondary antibody. Specific IgG antibody was detected by rSsCLP5-based indirect ELISA as previously described [ 37 ]. The results showed that the specific IgG antibodies increased at one week after the first vaccination in the rSsCLP5 vaccine groups, and levels were significantly higher than the antibody levels of three control groups ( F (5,63) = 37.285, P < 0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal conditions for the rSsCLP5-based indirect ELISA were determined to be 4 μg/ml of rSsCLP5 protein, a 1:120 serum dilution, and a 1:3000 dilution of secondary antibody. Specific IgG antibody was detected by rSsCLP5-based indirect ELISA as previously described [ 37 ]. The results showed that the specific IgG antibodies increased at one week after the first vaccination in the rSsCLP5 vaccine groups, and levels were significantly higher than the antibody levels of three control groups ( F (5,63) = 37.285, P < 0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, heat-induced epitope retrieval was accomplished by immersing sections in 0.01 M sodium citrate buffer (pH 6.0) at 95 °C for 20 min. The sections were incubated in blocking buffer (5% bovine serum albumin in PBS) for 1 h at room temperature before incubation overnight at 4 °C with specific rabbit anti-rSsCLP5 antibodies (preparation of rSsCLP5 polyclonal antibody as described previously [ 37 ]) covering the sections (diluted 1:100 in PBS). After washing three times with PBS, the sections were incubated with fluorescein isothiocyanate (FITC) goat anti-rabbit IgG (H+L; diluted 1:100; EarthOx, LLC, San Francisco, CA, USA) in 0.1% Evans Blue for 1 h at 37 °C in the dark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordinary scabies (OS) and CS are two forms of scabies. OS is usually caused by a few mites, which makes the diagnosis very difficult, while CS is easy to diagnose based on the large number of mites and obvious clinical symptoms [ 8 , 9 ]. The development of serodiagnosis has seen serological diagnostic kits using mite extracts becoming commercially available [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Allergens are the main factors eliciting the hosts pro-inflammatory response, and most of the allergen genes are hydrolase genes, having crucial roles in mite evasion and survival in the host [20, 21]. Moreover, there are several allergen and hydrolase genes in mites which have been identified to be potential diagnostic antigens and vaccine candidates [2225]. Intriguingly, analysis of C. texanus allergen and hydrolase genes may provide a valuable database for exploring new potential diagnostic, prevention and treatment methods.…”
Section: Introductionmentioning
confidence: 99%